Social inference in individuals at clinical high risk for psychosis. Issue 1 (9th September 2014) - Gill, Kelly E.; Cressman, Victoria; Poe, Sarah Lucy; Steinfeld, Sara; Ben‐David, Shelly; G. Keilp, John; Moore, Holly; Turkstra, Lyn S.; Corcoran, Cheryl
Abstract: Aim: Social cognition impairment is a hallmark of schizophrenia and contains multiple domains. The domain of social inference has been relatively understudied in schizophrenia and its risk states. Methods: Social inference was assessed in 60 clinical high‐risk (CHR) patients and 28 healthy control subjects, using the video social inference task. We hypothesized a deficit in social inference in CHR participants and examined predictive value for psychosis transition. Results: Social inference was positively associated with increasing age. Social inference did not differ significantly between CHR patients and controls, or predict transition to psychosis. Conclusions: Few studies have examined social inference of individuals at clinical high risk for psychosis, and findings have been inconclusive. Additional studies using a variety of measures of social inference in CHR participants are recommended.